Impact of learning support intervention on preclinical students' conception of self-regulated learning: A quasi-experimental study based on the Motivated Strategies for Learning Questionnaire / Radha Kodiappan - Radha, Kodiappan (2020)
Self-regulated learning (SRL), which includes the ability to regulate motivational, cognitive and metacognitive strategies based on the contextual and task demand, is recognized as a critical element for lifelong learning. However, past literature indicate a deficit in undergraduate medical students’ capabilities to self-regulate their learning and shortcoming of implicit methods to develop students’ SRL in medical schools. Thus, the objectives of this research were to analyse (i) the baseline level of the preclinical students’ SRL and (ii) the impact of the learning support intervention on the students’ conception of SRL. These objectives were approached from the perspectives of the students’ motivation orientation and learning strategies. Understanding the impact of this intervention on the students’ SRL conception will enable opportunities for medical teachers to plan and design effective learning support programmes that will enrich the students’ lifelong learning skills. In this one-group pretest-posttest quasi-experimental research involving explicit training on SRL strategies, the Motivated Strategies for Learning Questionnaire (MSLQ) was administered to the first-year, and second-year undergraduate medical students at the Perdana University-RCSI School of Medicine, Malaysia. A total of 53 students participated in this research. The baseline level of the preclinical students’ motivation and learning strategies for SRL were determined based on the descriptive statistics analysis of the pre-test MSLQ data. The findings revealed that the preclinical students had high task value and control beliefs. However, they were extrinsically motivated and reported low self-efficacy beliefs. Although the data showed that the students do use some higher-order cognitive learning strategies such as organization and elaboration, the high dependence of surface learning strategies such as rehearsal, and the deficits in critical thinking, metacognitive self-regulation, and resource management strategies were indicative of inefficient self-regulation of learning among iv the preclinical students. The independent t-test and the Mann-Whitney test showed no significant difference in the baseline level of SRL between the first-year and second-year students. The paired-sample t-test and Wilcoxon signed-rank test revealed that the intervention significantly reduced students’ test anxiety and significantly increased the post-test mean scores for all subscales, except effort regulation and extrinsic motivation. Notably, the explicit SRL teaching favourably enhanced the students’ self-efficacy beliefs and extrinsic motivation to self-regulate their learning. Hence, medical schools should take serious consideration on imparting explicit learning skills instruction as it can positively impact the students’ motivation and learning strategies to effectively selfregulate their learning.